ICERD and Old Politics : New Twists in Post-Election Malaysia? - Waikar, Prashanta (2018)
The Malaysian government’s move not to ratify the International Convention for the Elimination of Racial Discrimination (ICERD) despite an earlier decision to do so has dominated headlines. The events surrounding the ICERD imbroglio reveals three new political developments in post-election Malaysia.